Study on Supporting Protection of Tunnel Opening near a Rock Layer under Elastic Deformation of Surrounding Rock - Zhigang Jia; Yongsong Li (Geofluids)
Due to the limitation of geological conditions and route alignment, tunnel engineering will inevitably pass through special sections such as shallow buried section, broken rock layer, and loss and weak rock stratum. Tunnel construction in these special sections will easily lead to tunnel collapse, landslide of portal slope, excessive deformation of supporting structure, and even deformation and damage accidents, which are high-incidence areas of engineering safety accidents. In this paper, a 3D numerical model is established based on a practical engineering to analyze the deformation and stress variation of surrounding rock of the tunnel with the in-advance support technology. According to the monitoring results of the actual project, the deformation law of the soft rock section at the tunnel entrance is mastered. The deformation of surrounding rock of the tunnel under the support condition of changing the three main parameters, such as ring spacing, pipe diameter, and pipe length, is analyzed, and the effect of controlling the deformation of surrounding rock with different parameters is studied. The deformation, stress characteristics, and plastic zone distribution of surrounding rock by a single side wall guide method and ring excavation and retaining core soil method in advance support are numerically simulated and studied.